Respiratory syncytial virus: current and emerging treatment options - Turner TL; Kopp BT; Paul G; Landgrave LC; Hayes D Jr; Thompson R (Dove Medical Press, 2014)
Tiffany L Turner,1 Benjamin T Kopp,1 Grace Paul,1 Lindsay C Landgrave,2 Don Hayes Jr,1 Rohan Thompson11Department of Pediatrics, Ohio State University College of Medicine, 2Clinical Pharmacy, Nationwide Children's Hospital, Columbus, OH, USAAbstract: Respiratory syncytial virus (RSV) is an important respiratory pathogen in infants and children worldwide. Although RSV typically causes mild upper respiratory infections, it frequently causes severe morbidity and mortality, especially in premature infants and children with other chronic diseases. Treatment of RSV is limited by a lack of effective antiviral treatments; however, ribavirin has been used in complicated cases, along with the addition of intravenous immune globulin in specific patients. Vaccination strategies for RSV prevention are heavily studied, but only palivizumab (Synagis®) has been approved for use in the United States in very select patient populations. Research is ongoing in developing additional vaccines, along with alternative therapies that may help prevent or decrease the severity of RSV infections in infants and children. To date, we have not seen a decrement in RSV morbidity and mortality with our current options; therefore, there is a clear need for novel RSV preventative and therapeutic strategies. In this review, we discuss the current and evolving trends in RSV treatment for infants and children.Keywords: bronchiolitis, lower respiratory tract infection, respiratory syncytial virus, probiotics, vitamin D